2007
DOI: 10.1158/1078-0432.ccr-06-2736
|View full text |Cite
|
Sign up to set email alerts
|

Sex Chromosome Alterations Associate with Tumor Progression in Sporadic Colorectal Carcinomas

Abstract: Purpose: The X and Ychromosomes have been associated with malignancy in different types of human tumors. This study attempts to determine the involvement of X chromosome and pseudoautosomal regions (PAR) in sporadic colorectal carcinogenesis. Experimental Design: An allelotyping of X chromosome in 20 premalignant and 22 malignant sporadic colorectal tumors (CRC) from female patients and an analysis of losses [loss of heterozygosity (LOH)] on PARs from 44 CRCs and 12 adenomas of male patients were carried out. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…At the present time, however, it is difficult to know, which genes are of significance in feminized CRCs due to the large genomic areas affected by the X chromosomal aberrations. With respect to the Y chromosome losses in male CRC observed here, other studies also support our findings [11,12,48]. …”
Section: Discussionsupporting
confidence: 92%
“…At the present time, however, it is difficult to know, which genes are of significance in feminized CRCs due to the large genomic areas affected by the X chromosomal aberrations. With respect to the Y chromosome losses in male CRC observed here, other studies also support our findings [11,12,48]. …”
Section: Discussionsupporting
confidence: 92%
“…Loss of the entire Y chromosome (LOY) has been reported with various frequencies in prostate [133][134][135] , pancreatic 136 , colorectal 137 and bladder 138 , which has also a strong male prevalence. Short arm deletions have also been found in numerous cancer types 139 (http://cgap.nci.nih.gov/Chromosomes/Mitelman).…”
Section: B) Y Chromosomementioning
confidence: 99%
“…In ICGCTs, the gain of X/Y chromo- somes in the tumors could result in gene dosage effects caused by genomic rearrangements as well as by mutations in yet unknown genes leading to activation of oncogenes or loss of function of tumor suppressor genes (Skaletsky et al, 2003;Spatz et al, 2004;Hanks and Rahman, 2005). Recent data have shown that some sporadic colorectal cancers exhibit X chromosome abnormalities suggesting the participation of putative tumor suppressors within PARs (pseudoautosomal regions) (Bottarelli et al, 2007). In summary, our findings support the notion that ICGCTs are associated with KS and emphasize that sex chromosome aneuploidies participate in both tumorigenesis and cancer progression.…”
Section: Discussionmentioning
confidence: 99%